The Capacity of Private Universities in Nigeria - Arikewuyo, M. Olalekan; Ogunsanwo, Mojisola (International Journal of Educational Management, 2022)
The study examined the capacity of private universities in Nigeria. Data for the study were gathered from the National Universities Commission (NUC), the regulatory body for all universities (both public and private) in Nigeria. Findings revealed that as at 2017, there were 68 private universities in the country. Furthermore, the total student enrolment for all the 146 public and private Universities in Nigeria was 1,962,364, out of which the private universities had 104,454, which is 5.32 percent. This shows that the capacity of private universities in Nigeria is very low. The study observed that in spite of the challenges being faced by the institutions, Nigerians will continue to recourse to private Universities, because the public Universities are unable to offer admission to all the qualified candidates in the country. Specifically, two of the first generation private Universities (Madonna and Babcock) had the highest student enrolment of 12,444 and 9988 respectfully. The study recommended that private Universities should pay attention to issues of quality, so as to continue to be relevant in the Nigerian educational system.